SUGGESTING THE ISLAMIC LAW APPROACH TO THE PRACTICE OF EUTHANASIA IN NIGERIA - Yusuph, Ismael Funsho; Abdulazeez, Abdurrozaq Opeyemi; Ahmad Tijani, Abubakar Sheu (Jurnal Syariah, 2023)
Advancements in both medical technology and bioethics have generated various new moral issues regarding abortion, cloning, and euthanasia. Arguments on euthanasia often hinge on the ‘right to life’ and the ‘right to die’. The first is a widely accepted basic human right and moral value, based on the fact that people generally want to live. However, what should be the case when seriously ill people choose to die because of unbearable pain? This concerns both medical and religious ethics and it becoming more pressing recently. How can a balance be maintained between the right to life and making death an alternative for a sick person experiencing unbearable pain? This, therefore, forms the premise under which this paper is written from the perspectives of Islamic ethics vis-à-vis medical ethics. The objective of this paper is therefore to consider the Islamic ethical position on euthanasia to appreciate its comprehensiveness and investigate medical treatment and practice of euthanasia. While adopting doctrinal and non-doctrinal methods, the findings of this study show that many people particularly in Nigeria unwittingly practice passive euthanasia as a result of religious doctrine or economic disadvantage. The study concludes that Allah grants human beings the right to live but not the right to die under any circumstance and that nature be allowed to take its course.